Pengaruh Atribut Produk Terhadap Keputusan Pembelian Melalui Sikap Dan Minat Sebagai Variabel MediasiPada Konsumen Buah Jeruk Lokal Di Kota Malang - Illu, Abraham Ruylthon; Eldisthia, Erika (Jurnal Ekonomi Pertanian dan Agribisnis, 2024)
This article attempts to look specifically at the effect of product attributes on purchasing decisions through attitudes and interests as mediating variables for local citrus fruit consumers in Malang City. The method used in this article is a type of quantitative research using Structural Equation Modeling (SEM) analysis with the Warp Partial Least Square (WarpPLS) approach. In addition, the Sobel Test is also used to test the significance value of the indirect relationship between product attributes and purchasing decisions mediated by attitudes and interests. Primary data was obtained by distributing questionnaires online. Meanwhile, secondary data was obtained through literature studies from various related sources. Determination of the sample was carried out using a purposive sampling technique so that 124 people were selected as respondents in this study. The results of the analysis show that the indirect effect of product attributes through consumer attitudes and consumer interest on purchasing decisions for local citrus fruits in Malang City is significant. The results of the analysis also show that the consumer attitude variable and consumer interest variable have a partial mediating effect on product attributes in influencing local citrus fruit purchasing decisions in Malang City.